Metaphysical Preconditions of Transcendental Psychology of Perception - Naghdyan, Ruben (Bulletin of Yerevan University E: Philosophy, Psychology, 2013)
The given article deals with the sources of transcendental psychology of perception of A. I. Mirakyan. The content of his approach to the study of psychic reflection is revealed. It is considered that the solution to the problem on the origin of the psychic and the definition of the subject of Psychology is an interdisciplinary one.